Metallation‐Induced Heterogeneous Dynamics of DNA Revealed by Single‐Molecule FRET. Issue 22 (9th March 2020) - Berrocal‐Martin, Raul; Sanchez‐Cano, Carlos; Chiu, Cookson K. C.; Needham, Russell J.; Sadler, Peter J.; Magennis, Steven W.
Abstract: The metallation of nucleic acids is key to wide‐ranging applications, from anticancer medicine to nanomaterials, yet there is a lack of understanding of the molecular‐level effects of metallation. Here, we apply single‐molecule fluorescence methods to study the reaction of an organo‐osmium anticancer complex and DNA. Individual metallated DNA hairpins are characterised using Förster resonance energy transfer (FRET). Although ensemble measurements suggest a simple two‐state system, single‐molecule experiments reveal an underlying heterogeneity in the oligonucleotide dynamics, attributable to different degrees of metallation of the GC‐rich hairpin stem. Metallated hairpins display fast two‐state transitions with a two‐fold increase in the opening rate to ≈2 s −1, relative to the unmodified hairpin, and relatively static conformations with long‐lived open (and closed) states of 5 to ≥50 s. These studies show that a single‐molecule approach can provide new insight into metallation‐induced changes in DNA structure and dynamics. Abstract : Dynamic complexity : The metallation of DNA by an organo‐osmium anticancer complex is studied using single‐molecule Förster resonance energy transfer (FRET), revealing dynamic heterogeneity that is obscured at the ensemble level.